A proper application of chemotherapeutic agent at the site of anal fissure: a major concern in healing anal fissure - Mannan, Ambreen; Jarwar, Muhammad; Soomro, Suhail Ahmed (International Surgery Journal, 2019)
Background: To show the efficacy of chemotherapeutic agent by special emphasis on its proper application at the site of anal fissure. Methods: All patients were seen in outpatient department and were initially started with 0.2% Glyceryl trinitrate ointment along with sitz bath and psyllium fiber as a primary treatment while 2% diltiazem cream reserved for refractory cases. The follow up visits were made weekly for perianal pain relief and ulcer healing rate. Results: Results in terms of healing of anal fissure and perianal pain relief in 2 or 4 weeks duration were recorded in SPSS version 17. 0.2% GTN ointment showed 75% results in 2 weeks. While complete response was achieved in 95% cases in 4weeks. 2% diltiazem responded in 98% cases in 2 weeks. Non-compliant (2%) abandoned the medical treatment early in the course and proceeded for surgery where 99.99% results were seen in 2weeks only. Conclusions: Conservative treatment is the gold standard for managing anal fissure. Effective counseling of proper application of ointment at the site of anal fissure is emphasized, which is usually failed by the patient due to intense, excruciating peri anal pain and spasmodic sphincter contraction which led them to proceed to surgery.